2017
DOI: 10.1371/journal.pone.0178234
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status during pregnancy and postpartum

Abstract: ObjectivesDifferent studies have documented an association between periodontal disease and low birth-weight delivery. Hence, knowledge of periodontal status during pregnancy and postpartum is important in order to reduce the risks of both diseases. This study aimed to analyze periodontal status at successive stages of pregnancy and 3–6 weeks postpartum in women with initial periodontal alterations.Materials and methodsNinety-six pregnant women were examined at 8–10 weeks (pregnancy diagnosis, baseline), 21–23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 35 publications
2
53
0
7
Order By: Relevance
“…Pregnancy is a stage of life for women in which numerous physiological and lifestyle changes occur [3]. These changes are, in great measure, responsible for the manifestations that are produced in the oral cavity during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is a stage of life for women in which numerous physiological and lifestyle changes occur [3]. These changes are, in great measure, responsible for the manifestations that are produced in the oral cavity during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent changes produced in the oral cavity during pregnancy are pregnancy gingivitis, with a prevalence of 60%-75% [3,5,6]; xerostomy, between 15% and 18% [4], pregnancy epulis, with a prevalence of approximately 5% [7]; dental erosion, which occurs in 75%-80% of cases [5], and halitosis, which is referred in around 13% of cases [8,9]. Likewise, the changes in dietary habits can be associated with an incremented risk of developing caries lesions or a progression of those already present [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…gebe hastalarda jinjival inflamasyonun arttığını ve periodontal durumun gebelikte bozulduğunu bildirmişlerdir. 32 Kesitsel ve kohort çalışmaları, benzer plak kontrolüne rağmen gebe olmayan kadın kontrol grubuna kıyasla, gebelerde jinjivit prevalans ve şiddetinin artmış olduğunu göstermektedir. 33,34 Çeşitli çalışmalar ile gebe kadınların ağız sağlığının yetersiz olduğu gösterilmiş ve periodontal hastalıklar, kadınlarda yaşam kalitesini düşürmesi nedeni ile üzerinde durulması gereken önemli halk sağlığı sorunlarından biri olarak belirtilmiştir.…”
Section: Discussionunclassified
“…The few studies of this nature are summarized in Table . These vary considerably in design; many did not include a non‐pregnant comparison group; others had a small sample size; some did not report baseline periodontal status; one provided no case definition for periodontitis; and one included only periodontally healthy participants . Even so, all those studies reported greater periodontal disease experience during pregnancy, followed by post‐partum improvement.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Epidemiological studies have suggested an association between parity (the number of times a women has given birth) and tooth loss, and parity and periodontal attachment loss, but none has determined whether this association is causal. A number of studies have reported greater severity and extent of gingival inflammation during pregnancy . While not offering evidence that the association is cause, these findings have fuelled the hypothesis that pregnancy and parity are risk factors for periodontal disease.…”
Section: Introductionmentioning
confidence: 99%